2003
DOI: 10.1007/s00330-003-1984-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging protocols for examination of the neurocranium at 3 T

Abstract: The increasing availability of high-field (3 T) MR scanners requires adapting and optimizing clinical imaging protocols to exploit the theoretically higher signal-to-noise ratio (SNR) of the higher field strength. Our aim was to establish reliable and stable protocols meeting the clinical demands for imaging the neurocranium at 3 T. Two hundred patients with a broad range of indications received an examination of the neurocranium with an appropriate assortment of imaging techniques at 3 T. Several imaging para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
1
25
0
6
Order By: Relevance
“…However, it has been shown that the use of SE sequences throughout the basal ganglia may significantly improve the sensitivity in the evaluation of patients with neurodegenerative disorders because of the increased sensitivity of SE sequences to magnetic susceptibility effects [8]. Recently, a new generation of whole-body MR imaging units with field strengths of 3.0 T has become increasingly available for routine imaging and currently is undergoing clinical evaluation [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the use of SE sequences throughout the basal ganglia may significantly improve the sensitivity in the evaluation of patients with neurodegenerative disorders because of the increased sensitivity of SE sequences to magnetic susceptibility effects [8]. Recently, a new generation of whole-body MR imaging units with field strengths of 3.0 T has become increasingly available for routine imaging and currently is undergoing clinical evaluation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Given some disadvantages of 3T units, such as specific absorption rate (SAR) limitations and low contrast between gray and white matter of the brain on T1-weighted SE images, GE techniques that allow lower SAR, higher gray-white contrast, and rapid acquisition of 3D images are generally used for T1-weighted brain imaging at 3T. 5,6 Furthermore, because the contrast enhancement effect at 3T is higher than that at 1.5T, several studies have suggested that 3D contrast-enhanced GE images provide higher detectability of small brain metastases than 2D contrast-enhanced SE T1-weighted images when a 3T system is used. 7,8 Although high SAR at 3T makes it difficult to obtain T1-weighted 3D images with an SE-type sequence, recent technologic innovations, including parallel imaging, k-space trajectory, and variable flip angles, have solved the problem.…”
mentioning
confidence: 99%
“…12,13 In this study, we applied VBM analysis to brain images acquired with a 3-T magnet to investigate whether changes in GM density are present in migraine patients with evidence of WM damage on conventional MRI compared with healthy controls. In case such changes were detected, additional analysis was preplanned in an attempt to provide some clues about their nature through the investigation of their correlation with patients' demographic characteristics (age, disease duration), clinical manifestations of the disease (presence/absence of aura), and extent of macroscopic visible lesions.…”
mentioning
confidence: 99%